Effect of Sodium Dodecyl Sulfate on the Supramolecular Complexation Between Chitosan and b-Carotene - Kongsri, S.; Techawongstein, S.; Chanthai, S. (Asian Journal of Chemistry, 2012)
The chemical interactions between b-carotene and chitosan were investigated by using resonance light scattering intensity and Fourier transform infrared (FT-IR) spectroscopic methods. The optimum conditions for its aggregation and followed by flocculation were obtained. An ethanolic solution of b-carotene (14 μM) was added into an acidic solution of chitosan (4 mM) in acetate buffer solution pH 5 and heated at 40 ºC for 0.5 h. Under the weak acidic conditions, b-carotene was induced to interact with chitosan to form a stable aggregated complex. The effect of sodium dodecyl sulfate (2 mM) in association with other experimental parameters significantly affected their interactions. However, the soluble aggregated complexes were inductively become larger aggregates causing phase separation. It was found that the soluble aggregated complex became to be a labile supramolecular complex flocculating under the critical conditions. Regarding to FT-IR spectrum, it exhibited their characteristics of the supramolecular aggregated complex.